Effects of the Bull on Conception Rate of Dairy Cows in Different Seasons and According to AI Type - Luz, Gabriela Bueno; Maffi, Andressa Stein; Farias, Lucas Balinhas; Xavier, Eduardo Goulart; Lima, Márcio Erpen; Corrêa, Marcio Nunes; Brauner, Cássio Cassal (Acta Scientiae Veterinariae, 2018)
Background: Reproductive efficiency is one of the most important factors affecting the performance dairy cattle, and fixedtime artificial insemination (TAI) is an important biotechnology factor employed in bovine livestock. The achievement of satisfactory results in TAI protocols depends of several factors, such as health and body condition, milk yield, environmental temperatures, ovulation time, semen manipulation, as well as semen quality. The goal of this study was to evaluate the conception rate of heifers and multiparous cows based on different Holstein bulls used for artificial insemination (AI). The effects of the type of management AI, animal category, and season of the year were also examined. Materials, Methods & Results: A three-year database on the reproductive management of a dairy farm was formed. All the cows and heifers were of the Holstein breed, in semi-intensive nutritional management, milked twice a day, and received a total mix ration. After 45 days in milk, when cows were observed twice daily with estrus signs, posterior artificial insemination occurred 12 h after estrus visualization was made. However, cows that were not observed in estrus were submitted to a timed artificial insemination (TAI). In this study, these fixed factors were considered: bulls utilized for the AI (totalizing 10 animals with at least 100 inseminations in each season, denoted by the letter B and a number - B1, B2, B3, B4, B5, B6, B7, B8, B9, B10); the season of the insemination (spring/summer being from November to April and autumn/winter from May to October), category animal (heifers, animals that never have been calved, or multiparous, animals that have already given birth more than once), and the type of AI (which included TAI using a protocol for synchronization, but cows having not necessarily shown estrus signs at the AI; ETAI: using protocol of synchronization, cows showing estrus signs at the AI; and AI with estrus visualization, without protocol of synchronization when animals were observed in estrus and were inseminated 12 h later. The fertility parameter of the bulls and reproductive performance in AI was based on conception rate. There was a statistical difference among different bulls in the same season (P ≤ 0.05). There was also a difference in reproductive performance of the same bulls between seasons, autumn/winter and spring/summer; B8 37.8% vs. 32.0% (P = 0.05) and B10 35.1% vs. 20.7% (P = 0.003). Regarding the individual animal category, only one bull (B6) demonstrated higher reproductive performance when utilized in the AI of heifers than multiparous 39.2% vs. 27.2% (P = 0.01). Similarly, regarding the effect of the type of AI, only one bull (B8) exhibited different results, obtaining better results for conception rate when utilized in fixed TAI with estrus visualization (35.5%) and in the AI with estrus visualization (39.0%) compared with that of TAI (19.9%) (P < 0.05). Discussion: From these results, it was observed that some bulls exhibited better performance in situations of greater challenge. In addition, some animals presented variation in efficiency with the demonstration of estrus or not. Therefore, bulls that present semen with higher fertility in certain types of AI could be utilized on a larger scale for to increase the reproductive rates in artificial insemination. The results of this study indicate that despite the tests indicating the semen that is submitted is adequate, there are still variations in quality and the reproductive efficiency of each bull. With the effects varying based on fertility and on different environmental and management situations.